A Study of the Effects of China's TBT Notifications on Korean Exports - Bai, Yun; Oh, Keunyeob (International economic journal, 2023)
Since China joined the World Trade Organization (WTO) in 2002, the number of technical barriers to trade (TBT) notifications has increased rapidly. This study investigates the impact of China's imposition of TBTs on the exports of Korean manufacturing-industry from 2002 to 2014. We focus on the following aspects: exports in terms of value-added, a comparison of exports of final goods with exports of intermediate goods, and specific trade concerns (STCs). Our findings are as follows. First, China's TBTs have an insignificant impact on Korean manufacturing exports to China when we investigate the whole manufacturing industry sector. Second, as a result of analyzing final goods and intermediate goods separately, we do not find a significant effect of TBTs on the export of intermediate goods, whereas they have negative effects on the export of final goods. This is in line with our expectations that China does not want to restrict the import of intermediate goods. Third, further analysis of the relationship between exports and TBT STCs is conducted. However, we find no additional negative effect of TBT STCs on exports. Fourth, the impact of TBTs on exports in value-added terms does not seem to differ from the impact on total gross exports.